Performance Assessment of Sugar Beet (Beta Vulgaris L.) for Root and Yield Characters in Humid Tropics (London Journal of Research In Science: Natural and Formal, 2025)
A study was conducted to assess the performance of sugar beet in humid tropical regions and to identify varieties/ hybrids, suitable to tropical conditions. The experimental material consisted of 30 sugar beet genotypes, including twenty-two varieties and eight hybrids. The experiment was laid out in RBD with three replications. Analysis of variance revealed significant differences among the twenty-two varieties and the eight hybrids for all the characters studied. Madhur recorded the highest root length of 7.43 cm among varieties and Red Star (Sakura) (7.41 cm) among hybrids. The highest root diameter of 5.33 cm was also recorded by Madhur and Ruby Queen (Tokita) (5.25 cm), Detroit Dark Red (5.16 cm) and Mahyco Lal ?? (5.15 cm) were statistically on par with it. The hybrid Red Star (Sakura) recorded the highest root diameter of 5.50 cm, which was on par with Ragini (5.32 cm). Madhur, among varieties and Red Star (Sakura), among hybrids recorded the highest root length (7.43 cm, 7.41 cm), root diameter (5.33 cm, 5.50 cm), root weight (118.05 g, 91.27 g), root: shoot ratio (4.42, 3.61) and yield per plot (5.68 kg, 4.27 kg), respectively. The varieties, Madhur, Tetra and Ruby Queen (Tokita) were early with a crop duration of 96 days, while the hybrids, Red Star (Sakura), Red Horse and RK 777 were early with a crop duration of 98 days. Madhur and Red Star (Sakura) were adjudged as the best performing variety and hybrid respectively, suitable for growing under humid tropical conditions.
Keywords: pollution; Soil; heavy metals; Siret River sides; propagation; rooting; growth powders; auxins.; sugar beet; tropical varieties; tropical hybrids; mean performance; root yield